In vitro and in vivo Antiamoebic Potential of Actinopyga lecanora (Jaeger) (Bangladesh Pharmaceutical Journal, 2015)
Human amoebiasis, due to Entamoeba histolytica infection, is mainly associated with morbidity thus affecting the quality of life and pace of development in the countries with warm climatic conditions. So far, the available drugs provide only symptomatic relief and they are not devoid of side effects. This leads to obtain novel molecules from natural sources having antiamoebic activity. The methanol extract of Actinopyga lecanora (Jaeger) displayed antiamoebic activity. It showed MIC 125 ?g/ml in our in-vitro studies, but when it was tested in rats, it revealed 88% inhibition of trophozoites at the dose of 900 mg/kg body weight against Entamoeba histolytica. Further work is in progress for the isolation and characterization of active molecules.Bangladesh Pharmaceutical Journal 18(2): 118-120, 2015